Instructional Strategies Toward Real-Time Online Teaching at an Informal English Institution: An Explanatory Study on Instructional Strategies - Noviani, Stella (JET (Journal of English Teaching), 2021)
Studies on teachers’ self-regulation are abundant and still posit strategic relevance for teacher professional development. Nevertheless, such studies focusing on online learning are yet underrepresented within informal education contexts. Hence, this study aimed to investigate the teachers’ self-regulation in implementing the instructional strategies in real-time online teaching. This study was undertaken in an English course in an informal institution during the COVID-19 pandemic. Using the explanatory sequential method, the data were collected from sixteen teachers with different levels of classes in teaching, nine of whom are full-timers and seven part-timers. A set of questionnaires was adapted from TSRS (Teacher Self-Regulation Scale) by a five-point Likert scale to accommodate two variables, namely: (1) the strategies as self-regulated teachers, (2) the relation between the teacher’s self-regulation and instructional strategies in real-time online teaching. The other two open-ended questions were addressed to support the quantitative data. The findings demonstrate that the role of teacher’s self-regulation in teaching and implementing instructional strategies is essential in real-time online teaching. This concludes that the higher the self-regulation, the better it is for the mastery of instructional strategies and the positive output of real-time online teaching.